Two-phase oil/water flow measurement using an Earth's field nuclear magnetic resonance flow meter. (20th July 2019) - O'Neill, Keelan T.; Brancato, Lorenzo; Stanwix, Paul L.; Fridjonsson, Einar O.; Johns, Michael L.
Highlights: Earth's field NMR flow meter used to simultaneously measure oil and water flowrates. Dual polarisation mechanism introduced to allow T 1 phase differentiation. 2D signal inversion method used to determine velocity- T 1 probability distributions. Accurate flowrate measurements captured in three oil/water flow regimes. Abstract: We present a novel multiphase flow metering technique for simultaneous measurement of oil and water volumetric flowrates. An Earth's field nuclear magnetic resonance (NMR) detection coil is applied to measure free induction decay (FID) signals of two-phase oil/water flows. A dual polarisation technique is introduced utilising an upstream permanent magnet as well as an electromagnetic pre-polarising coil. FID signals with variable pre-polarising conditions are acquired and fit with a model for the NMR fluid signal using a 2D Tikhonov regularisation algorithm, allowing determination of a joint 2D velocity- T 1 probability distribution. Appropriate analysis of the measured velocity- T 1 distributions allows calculation of individual phase flowrates. The performance of the NMR flow measurement technique is examined for oil/water flows which are visually observed to be in three different flow regimes: stratified flow with mixing, dispersion of oil-in-water and water, and full oil-in-water emulsions. Two-phase flow characteristic features such as velocity slip are examined for each flow regime. Finally the accuracy of the measurement system in each flow regime is validated against in-line rotameter measurements.